Individual forecasting of reliability of bipolar transistors by using electrical voltage as a simulation factor - S. M. Borovikov; E. N. Shneiderov; A. I. Berasnevich; V. O. Kaziuchyts (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
Individual forecasting of the reliability of semiconductor devices, taking into account gradual failures, is an urgent task, as it allows you to choose highly reliable instances for critical electronic devices of long-term functioning. In relation to bipolar transistors, an approach is proposed that allows us to solve this problem by using the voltage applied to the collector-emitter junction as a simulated effect. Using the example of highpower bipolar transistors of the KT872A type, it is shown how the problem is solved. For the sample of transistors of this type using the results of a training experiment, two equations were obtained to describe the electrical parameter under consideration (a static base current transfer coefficient in a circuit with a common emitter), the value of which judges the absence or presence of a gradual failure for a specific instance. The first equation shows how the electrical parameter changes on average depending on the voltage applied to the collector – emitter junction. The second equation describes the average degradation of the electrical parameter during long-term operating time of transistors. Based on these two equations, a simulation model of the reliability of bipolar transistors of the type in question is obtained in the form of a communication function that shows what level of simulation voltage corresponds to a given operating time. As applied to the transistors of the type under consideration, the obtained simulation model allows us to individually predict reliability by the gradual failures of the same type of samples that did not participate in the training experiment. To do this, first determine the value of the simulation voltage corresponding to a given operating time. This is achieved by substituting a given operating time into the model. The individual forecasting of the reliability of a new onetype instance consists in measuring the electrical parameter of this instance at a voltage on the transistor collector corresponding to the calculated simulation value, and comparing the measurement result with the norm set on the electrical parameter.